Faktor-Faktor Yang Memengaruhi Struktur Modal - Mettalina; Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to examine the influence of firm size, liquidity, profitability, sales growth, and tangibility toward capital structure in manufacturing companies listed in the Indonesian Stock Exchange in the period 2017-2019. Sample was selected using purposive sampling method and the valid data was 35 companies. Data processing techniques using multiple linear regression what helped by Eviews program version 10 and Microsoft Excel 2007. The results of this study indicate that liquidity, profitability, and tangibility have negative effect on capital structure, while firm size and sales growth have no effect on capital structure. The implication of this study is manager must pay attention to the factors that can affect the capital structure, because the optimal capital structure can attract investors’ attention.